ANALISIS TAHAP PEMBUKTIKAN TEOREMA STEWART PADA MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA UNIVERISTAS KATOLIK WIDYA MANDALA MADIUN - Kristanto, Vigih Hery (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2018)
The purpose of this research was to find out how the stage of proofing the Stewart theorem was conducted by students of the Mathematics Education Department at Catholic Widya Mandala University of Madiun. This type of research is qualitative research with descriptive data analysis. The number of research subjects consisted of three students. This study describes the stage of proofing Stewart's theorem by students. The data collection process begins with the subject being asked to prove Stewart's theorem and write down the process of proving Stewart's theorem on the answer sheet provided. From the results of data collection, it was found that the verification process carried out by the three students used the direct verification method, there were some similarities between the three students in initiating the verification process, namely: drawing a high line on a triangle and using the pythagoras theorem to add information used in the verification process, to proving that Stewart's theorem required precision when describing an algebraic form and understanding of algebraic concepts from numbers, to prove Stewart's theorem needed time according to the speed of thinking that proves, to prove the Stewart theorem required problem solving skills, logical thinking, critical, analytical and systematic. Thus it can be concluded that, in general the steps of proving Stewart's theorem carried out by students of the Mathematics Education Department, starting with drawing ABC triangles and also describing auxiliary lines (high of CE), collecting information used in the verification process, then use the information obtained to describe the shape of the right side of the equation becomes the left hand side, so that the equation applies.